2019
DOI: 10.1021/acs.joc.9b00462
|View full text |Cite
|
Sign up to set email alerts
|

C–H Functionalizations by Palladium Carboxylates: The Acid Effect

Abstract: Finding optimal reaction conditions is usually complex, requires many experiments and is therefore demanding in terms of human, financial and environmental resources. This work provides a simple workflow for easier design of popular palladium catalyzed C-H functionalization reactions, where the active palladium catalysts contain carboxylate ligands. The key factor for optimizing reaction conditions is to find a balance between two opposing effects of the carboxylic acid in the reaction mixture; generation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Since C–H activation is usually involved in the rate-determining step (RDS), [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] we hypothesized the relative free energy of transition states of C–H cleavage (ΔG TS ≠ ) can determine the reactivity. The CMD mechanism was chosen for C–H activation, which usually has the lowest barrier among the frequently proposed mechanisms [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since C–H activation is usually involved in the rate-determining step (RDS), [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] we hypothesized the relative free energy of transition states of C–H cleavage (ΔG TS ≠ ) can determine the reactivity. The CMD mechanism was chosen for C–H activation, which usually has the lowest barrier among the frequently proposed mechanisms [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although impressive progress has been made, the scope of application of these strategies is still limited [ 36 , 37 ]. Using strong acid is also a widely used strategy to promote C–H activation; for example, palladium(II)-catalyzed ortho-selective C–H chlorination/bromination has demonstrated that proper strong acids (TFA, TfOH) could promote the reactivity of ortho-selective C–H bond cleavage ( Scheme 1 and Scheme 2 ) [ 25 , 26 , 27 , 28 , 29 , 30 , 38 , 39 , 40 ]. These experimental results showed that higher catalytic activity occurred in reactions with lower pKa value acids.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper by Jiří Váňa et al. highlighted the effect of the carboxylates on different aspects controlling reactivity of the palladium-catalyzed C−H activation (Váňa et al., 2019). The authors concluded that TFA can replace acetic acid on the metal, which would change the reactivity of the catalyst by increasing the electrophilicity of the palladium atom.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the combination of carboxylic acids and carboxylate salts afforded consistently high yields, among which sodium acetate and acetic acid proved to be optimal (entries 5–7). Presumably, the buffer was beneficial to provide a balance among palladium acetate species throughout the reaction 9 . Solvent screening indicated that DMA was the optimal medium (entries 8–10).…”
Section: Methodsmentioning
confidence: 99%